ANALISIS STRATEGI PEMASARAN JAGUNG HIBRIDA DI KABUPATEN BUTON (STUDI KASUS KECAMATAN LASALIMU SELATAN) - Azelia Monica Azizu (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2020)
Hybrid corn in South Lasalimu sub-district has problems, namely the lack of knowledge of farmers about hybrid varieties and still orientation to local corn cultivation, no information about the market so they still depend on local traders, lack of creativity and innovation for product management. The purpose of this study was to analyze internal and external factors that are threats, weaknesses, strengths and opportunities in marketing hybrid corn in South Lasalimu District, Buton Regency and to explain the marketing strategy of hybrid corn with SWOT analysis in South Lasalimu District, Buton Regency. This study uses a qualitative descriptive method with SWOT analysis. For the sampling used amounted to 50 people. The results of this study indicate that farming, especially hybrid corn in the district of South Lasalimu, has very good prospects. So there needs to be a development strategy that is more productive, efficient and effective and has good competitiveness. To be able to realize sustainable quality, it is necessary to have support from institutions that have goals in local and export markets. So it is necessary to really take advantage of resources to the fullest. The strategy that must be considered and strengthened is from a clear cultivation system, post-harvest, institutional, financial, cooperative and partner. If this is observed, then the income of hybrid corn farmers will increase.